INTEGRATING SUSTAINABILITY PRINCIPLES INTO MARITIME VOCATIONAL TRAINING: A FRAMEWORK FOR ENHANCING PORT AND SHIPPING EDUCATION - Guntoro, R. Herlan; Simanjuntak, Pargaulan Dwikora (Faculty of Administrative Science, Universitas Brawijaya, 2025)
Sustainability in maritime education is increasingly recognized as a critical component in preparing future maritime professionals for evolving environmental and operational challenges. This research examines the effectiveness of sustainability integration in maritime vocational training curricula, identifying key gaps between theoretical instruction and practical application. While previous studies have highlighted the need for sustainability education, limited research has assessed its direct impact on graduate readiness and industry alignment. The study aims to evaluate how sustainability principles are embedded within maritime training programs, focusing on curriculum integration, hands-on training, and industry expectations. Using a qualitative research methodology, data were collected from experts, lecturers, and graduates through semi-structured interviews, focus groups, and document analysis. A thematic analysis categorized findings into competency development, sustainability knowledge, and practical skill application. The results reveal an overall effectiveness score of 9/10, with curriculum integration scoring 9.2/10, yet practical training and graduate readiness scoring lower at 8.8/10 and 8.5/10, respectively. Despite strong institutional commitment, graduates face challenges in implementing sustainability practices in real-world settings. The study concludes that enhanced experiential learning, industry-academic collaboration, and sustainability certification programs are essential for bridging the gap between education and industry demands. These findings provide a structured framework for strengthening sustainability education in maritime vocational training, ensuring that future maritime professionals are equipped with the necessary skills and knowledge for sustainable port and shipping operations.